A Kreasi Non Alkohol Arak Jahe sebagai Produk Pendukung Wisata Halal: Indonesia - Syahdisa, M. Ardianto; Satiadji, Amirosa Ria; Dirga, Dewa Made (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Halal tourism is a set of additional amenities, attractions and accessibility services aimed and provided to meet the experiences, needs and desires of Muslim tourists. In order to accommodate the need for halal drinks with local potential, there is a traditional sweet Tuak drink which, with proper processing, is a non-alcoholic drink. Sweet Tuak is a traditional drink made from palm nira taken from sugar palm trees. The extract of water droplets from sugar palm is called nira, with a very sweet taste. Natural preservatives such as vinegar are also added to it, which functions to soak up the alcohol content in palm wine. The purpose of this research is to develop a drink that was initially just a simple drink or a fairly traditional drink, then the author developed it into a modern drink called a mocktail drink. The drink is made from sweet tuak, ginger, lime, egg white and butterfly pea. The method used by the author in this study is qualitative by involving several people who are experts in the field of hospitality, especially bartenders and baristas to test the results of the development of the drinks that the author makes. The development of this Traditional Drink Made from Sweet Tuak with Ginger is served using a champagne saucer glass to beautify the appearance of the drink which is 8 cm in diameter and 9 cm / 133ml high Sweet Tuak becomes a mocktail drink with the mass of the sweet tuak remaining for 6 hours if it is not refrigerated then when it is not cooled for more than 6 hours the alcohol content in the nira in the tuak manis will increase and become cocktail.